1995
DOI: 10.1136/gut.37.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Increased leucocyte adhesiveness/aggregation is a most useful indicator of disease activity in patients with inflammatory bowel disease.

Abstract: The aim of the study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…It is known that inflammation will confer increased adhesive properties upon WBC [26]and in a recent model of children with meningitis, it was shown that a significant correlation exists between the degree of cell aggregability and the concentration of IL1, IL6 and IL8 [23]. The previous observations that the LAAT was superior to the WBCC for discriminating between the presence or absence of an inflammatory response and between various intensities of this response [15, 16]further support the use of this functional marker. Indeed, we could use our image analyzer to differentiate effectively between the presence and absence of inflammation in elderly people based on leukocyte and erythrocyte aggregation [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that inflammation will confer increased adhesive properties upon WBC [26]and in a recent model of children with meningitis, it was shown that a significant correlation exists between the degree of cell aggregability and the concentration of IL1, IL6 and IL8 [23]. The previous observations that the LAAT was superior to the WBCC for discriminating between the presence or absence of an inflammatory response and between various intensities of this response [15, 16]further support the use of this functional marker. Indeed, we could use our image analyzer to differentiate effectively between the presence and absence of inflammation in elderly people based on leukocyte and erythrocyte aggregation [5].…”
Section: Discussionmentioning
confidence: 99%
“…Several groups of investigators have repeatedly shown that the LAAT is a sensitive marker of the presence of an inflammatory response and for the assessment of its intensity in various models of infection/inflammation, including rheumatic patients [15], inflammatory bowel diseases [16], bone infections [17], sepsis [18], trauma [19], infarction [20]and atherosclerosis [21]. Furthermore, it can be useful in the differentiation between viral and bacterial infections based on the observation that leukocyte adhesiveness/aggregation is augmented in patients with bacterial infections and not in viral ones [22, 23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…We had previously addressed the question of whether a functional test that is based on the adhesive properties of these cells might be of value for the diagnosis of the presence of an inflammatory response and for the assessment of its intensity [6]. It emerged that the leukocyte adhesiveness/aggregation test (LAAT), originally described as the leukergy test [7], is a sensitive marker of inflammation [6, 8, 9, 10]. In the present study, we examined the diagnostic potential of this test in a group of patients with nonviral infection/inflammation and no leukocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides that are present in bacterial walls as well as other mediators of in¯ammation have been shown to increase leukocyte adhesiveness and aggregation, 22 and the present study goes one step further in that it shows that this characteristic might have a diagnostic value. Although larger studies are needed to con®rm these preliminary observations, we do believe that a signi®cant increment in the adhesive function of the white blood cells re¯ects the presence of a more intense in¯ammatory response 23,24 and this is supported by studies that were performed by other groups. 21 Using this technique for the detection of individuals with a signi®cant bacterial infection, despite the absence of a markedly elevated leukocyte count, is an attractive possibility.…”
Section: Discussionmentioning
confidence: 67%